Neurosurgical Techniques for Disruption of the Blood-Brain Barrier for Glioblastoma Treatment - Analiz Rodriguez; Stephen B. Tatter; Waldemar Debinski (MDPI AG, 2015)
The blood-brain barrier remains a main hurdle to drug delivery to the brain. The prognosis of glioblastoma remains grim despite current multimodal medical management. We review neurosurgical technologies that disrupt the blood-brain barrier (BBB). We will review superselective intra-arterial mannitol infusion, focused ultrasound, laser interstitial thermotherapy, and non-thermal irreversible electroporation (NTIRE). These technologies can lead to transient BBB and blood-brain tumor barrier disruption and allow for the potential of more effective local drug delivery. Animal studies and preliminary clinical trials show promise for achieving this goal.